Towards a comprehensive model for liquid flow modulation in trickle bed reactors - Ayude, María Alejandra (2009)
The response of an isothermal TBR to a liquid flow modulation ON–OFF strategy is examined through a model aimed at the reactor scale. The reaction is gas-limited and first order with respect to both reactants. Liquid hydrodynamic behavior is considered by means of two different approaches: the Liquid Draining Approach, based on experimental results and the ideal, Square Wave Approach. Model allows the evaluation of, among other variables, the liquid holdup, the liquid velocity and the liquid reactant conversion time variations at different axial positions within the reactor. An enhancement factor due to periodic operation is defined by computing a temporal average of the liquid reactant conversion during an invariant cycling state, referred to its corresponding steady-state conversion. For all the conditions investigated, attainable enhancements are lower when the actual draining model is assumed.